PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA BADAN KEUANGAN DAERAH PEMERINTAH PROVINSI SUMATERA BARAT - Almi Zandria Alisna; Jhon Fernos (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2021)
This study aims to determine the effect of work environment and organizational culture on employee performance at the Regional Finance Board of the West Sumatra Provincial Government. The variables used in this study are the dependent variable, namely employee performance (Y), and the independent variable consisting of work environment (X1) and organizational culture (X2). The types of data used in this research are qualitative data and quantitative data. Accumulated data used in this study were primary data from questionnaires and used a proportional random sampling technique. The data analysis technique used classical assumption test, multiple linear regression analysis and t test. The population in this study were all employees of the regional financial agency of the province of West Sumatra, the sample in this study was 72 employees or respondents. The research data were collected from the respondents' results and analyzed using linear regression and hypothesis testing. The results of this study indicate that the work environment has a positive and significant effect on employee performance, with a t-count value of (3,342 > 2,000) and organizational culture has a positive effect on employee performance, with a t-count value of (3,336 > 2,000).